Gender and sexuality in knowledge organization systems: Proposal for a conceptual map - Borges Rodrigues Chagas, Leonardo; Aparecida Moura, Maria (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2024)
This article addresses the terms and concepts in knowledge organization systems related to individuals and social groups with sexual and gender identities that do not conform to cis-heteronormativity. Preliminary insights suggest that these concepts are not represented adequately in knowledge organization systems. Although advancements in gender and sexuality studies have occurred, these systems have not developed accordingly and as a result, hinder the recognition of the diverse range of sexual and gender identities thereby risking the perpetuation of prejudiced and discriminatory discourses about the respective individuals and groups. This exploratory qualitative study investigates terms and concepts reflecting terminological, social, and rights advancements relating to sexual and gender-diverse individuals. A bibliographic search was conducted in books, scientific articles, guides, and manuals addressing these advancements to support the construction of a conceptual map representation of the concepts. The study systematically structured representations hierarchically, beginning with overarching concepts and gradually delving into more specific ones. This approach was guided by a comprehensive understanding of the domain under analysis, ensuring clarity and accessibility for the reader. The organization of knowledge needs to incorporate gender and sexuality in the construction of knowledge organization systems so that diversity is adequately represented in these systems.